ANALYSIS OF THE TEACHING OF ARABIC LANGUAGE SCIENCES IN DYAH CLASS 3 OF THE TAKHASIS PROGRAM AT THE MODERN ISLAMIC BOARDING SCHOOL DARUL ARAFAH RAYA DELI SERDANG - Wandana, Nina; Lubis, Zulfahmi (Universitas Islam Negeri Sumatera Utara Medan, 2023)
The Takhasis Program at Darul Arafah Raya Islamic Boarding School aims to enhance the Arabic language comprehension of senior high school students through effective and innovative teaching methods. This study analyzes the implementation of Arabic language sciences instruction in the third-year Dyah class of the Takhasis Program using a descriptive qualitative approach, through observation, interviews, and documentation. The results show that both grammatical and communicative approaches are applied based on the students' initial abilities. Students with a general junior high school background face difficulties in understanding nahwu and sharaf, while those from Islamic junior high schools (MTs) have a better grasp of the material but still lack speaking skills. Students from Salafi pesantren have strong grammatical and textual proficiency but are weak in oral communication. Supporting factors include student motivation, a conducive boarding school environment, and teacher competence; whereas inhibiting factors involve differences in educational background, limited study time, and a lack of varied learning media. The study concludes that teaching strategies must be adapted to students' educational backgrounds, along with the effective use of diverse media and a supportive environment.